Enhancing Institutional Meals in Armed Police Force, Nepal - Karmacharya, Sachin (Journal of APF Command and Staff College, 2024)
This study explores the historical evolution and contemporary implementation of institutional meals within the Armed Police Force (APF), Nepal, tracing back to the early 1900s, when British mess provided food for soldiers and civil servants. It investigates the linkages between the Armed Police Force, Nepal, and nutrition, emphasizing the importance of providing officers with adequate sustenance for their well-being and operational efficiency. Through the introduction of a cash ration allowance system, the APF aims to empower its personnel to procure ration items in accordance with established guidelines. This qualitative inquiry conducted as part of Master’s Thesis in 2023, engages various APF personnel and stakeholders to examine the feasibility and challenges associated with institutional meal implementation. Employing both primary and secondary data collection methods, including semi-structured face-to-face interviews, key informant interviews, and focus group discussions, the study identifies key challenges and proposes strategies to address them. Notably, it suggests diversifying ration items based on factors such as altitude, training needs, and dietary preferences.